Social Design as a Function of Public Administration: Experience of the Project «Saint-Petersburg International Book Fair» - A. G. Shamrai (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
How can the political decision, as an element of public administration, fully and quickly solve the social problem about the values? The authors of the article suggest to consider similar experience in the field of education and culture on the example of the Saint-Petersburg International Book Fair as the element of the region strategy and as the method of solving social, marketing and image tasks.